HOW DOES THE ENERGY CRISIS AFFECT SMALL-SCALE INDUSTRIAL WORKERS IN DISTRICT SWAT, KHYBER PAKHTUNKHWA, PAKISTAN - Dr. Shahid Khan; Tariq Aziz; Israr Ahmad; Muhammad Arif Ullah; Ruqayya Bibi; Iqrar Ahmad (International Journal of Contemporary Issues in Social Sciences, 2024)
Electrical energy is perhaps one of the most pivotal sources that had pushed human being to a substantial growth and development around the globe. It is considered one of the major indicators in socio-economic development of a nation specially since, the development of power bulb and advance means of production. However, the higher dependency over electric sources had led to gap between the supply and demand ratio of electricity throughout the world, particularly in third world countries like Pakistan. Consequently, the country Pakistan observing acute shortage and thus leaded to heavy load shedding especially in the remote and rural area of the country. The unannounced and frequent shut down of electricity directly and indirectly effecting each and every sector especially, the industries and their laborers in a very large scale. The current study has carried out with major objective to scientifically investigate the effect of loadshedding on small scale industrial sector and their laborers in District swat of Khyber-Pakhtunkhwa, Pakistan. The nature of the study is qualitative however, the primary demographic information has disclosed in frequency and percentages. As per the requirement of the study the convenient sampling techniques has utilized for collection of information from sample respondents. Further, a total of 30 sample respondents constitutes the sample size where ten each from Marble, Plastic, Garment, Silk and Cosmetic industries were studied randomly. Moreover, interview guide encompassing all the study variable was followed as tool of data collection. The data was then analyzed thematically with supporting literature review and secondary information. The result of the data discloses that due to heave power outages the industrial sector of the region has collapsed leading thereby to socio-economic and psychological problems challenges for the workers. Due to such unemployment and poverty, it was difficult for the workers to maintain their family expenditures and activities of daily lives. To avoid industrial unemployment and uplift industrial growth in the country and especially in the region, the government shall be practical toward the development of power sector. Priority shall be given to hydro generation as well as the industrial sector to be declared exempt of load-shedding through-out he country.